Implementation Of Cambridge Worry Scale As A Psychological Assesment In Antenatal Care Routine - Ayu Nurdiyan; Yulizawati Yulizawati; Lusiana Elsinta Bustami; Detty Iryani; Aldina Ayunda Insani; fitrayeni fitrayeni (Universitas Andalas, 2016)
Pregnancy is a transition period in women’s life. In pregnancy, there are physiologic and psychological changes. Enhanced levels of anxiety during pregnancy may affect maternal blood flow and contribute to adverse obstetric, fetal and neonatal outcomes. There are many different reasons why women fell anxious and worry about their pregnancy. However, worries related to the pregnancy can contribute to high levels of pregnancy anxiety that has emerged as one of the most potent psychological predictors of adverse birth outcomes and is also implicated in poorer child and infant development.Pregnancy is a period in a woman’s life filled with pleasant anticipation of a baby, which may be influenced by several psychological stressors. Research on the psychological state in pregnancy indicates that each trimester of pregnancy includes possible stressors that may provoke several worries for pregnant women. Some studies found heightened levels of worries in the first and third trimester of pregnancy whereas others showed that each facet of a pregnant woman’s worries may fluctuate across the course of pregnancy. Several studies indicated that worries about the possibility of losing the baby, baby’s health, and childbirth are common causes of concerns among pregnant women. In addition to this kind of worries, there are other sources of worries in women daily life (e.g., worry about money, job, housing, their health, and marital relationships). Most women experience some mild worries during pregnancy; however, some women may experience pathological worries, defined as uncontrollable negative thoughts and excessive concern about future events in pregnancy which can produce anxiety.